Optimisation of the DNA dipstick as a rapid extraction method for Schistosoma japonicum in infected mice samples and spiked human clinical samples - Aula, Oyime P.; McManus, Donald P.; Jones, Malcolm K.; You, Hong; Cai, Pengfei; Gordon, Catherine A. (Infectious diseases of poverty, 2023)
Schistosomiasis remains a public health issue and the need for accurate and affordable diagnostics is crucial in the elimination of the disease. While molecular diagnostics are highly effective, they are expensive, with the main costs been associated with DNA extraction. The DNA dipstick is a rapid, affordable and simple purification method that allows DNA to be extracted from diagnostic samples within 30 s. We aimed to optimise the DNA dipstick method for samples from mice and egg-spiked human samples. Urine, blood and faeces were collected from mice exposed to Schistosoma japonicum infection at weekly intervals from Day 0 to Day 42. Urine and faecal samples were also collected from volunteer, uninfected humans and spiked with S. japonicum eggs. All samples were subject to several optimisation procedures and DNA extracted with the DNA dipstick. Amplification of the target DNA was carried out using LAMP and visualised using agarose gel electrophoresis and flocculation. The DNA dipstick successfully identified S. japonicum from infected mice and human clinical samples spiked with cracked eggs or genomic DNA from S. japonicum. Amplification was observed from week 4 post infection in infected mice. For human samples, amplification was observed in sieved faecal samples, filtered urine samples heated at 95 °C for 30 min, and sera samples heated at 95 °C for 30 min. The DNA dipstick combined with LAMP has huge potential in providing cost-effective, simple and accurate detection of schistosomiasis infection in endemic regions. This will allow for rapid treatment, tracking outbreaks-such as occur after typhoons, leading to better health outcomes and contributing to control and eventual elimination of schistosomiasis.